2017
DOI: 10.1007/s10886-017-0883-3
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Effects of Neonicotinoid Insecticide on Calling Behavior and Pheromone Production of Tortricid Moths

Abstract: In moths, sexual behavior combines female sex pheromone production and calling behavior. The normal functioning of these periodic events requires an intact nervous system. Neurotoxic insecticide residues in the agroecosystem could impact the normal functioning of pheromone communication through alteration of the nervous system. In this study we assess whether sublethal concentrations of the neonicotinoid insecticide thiacloprid, that competitively modulates nicotinic acetylcholine receptors at the dendrite, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…However, its control often requires the use of chemicals [ 6 , 7 , 8 , 9 ]. Finding valid and sustainable alternatives to insecticides is a key challenge for modern agriculture; side effects of insecticide use include environmental pollution, toxicity to non-target insects, and residues on food [ 10 , 11 , 12 , 13 ]. In this scenario, researchers are looking for new sustainable tools and products.…”
Section: Introductionmentioning
confidence: 99%
“…However, its control often requires the use of chemicals [ 6 , 7 , 8 , 9 ]. Finding valid and sustainable alternatives to insecticides is a key challenge for modern agriculture; side effects of insecticide use include environmental pollution, toxicity to non-target insects, and residues on food [ 10 , 11 , 12 , 13 ]. In this scenario, researchers are looking for new sustainable tools and products.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of MD, two major mechanism types have been proposed, competitive (CMD) which depends on the relative attraction of males to either MD pheromone dispensers or females, with no sensory impairment in either males (or females), and non-competitive (NCMD) where sensory disability of males (or females) reduces sexual activity 10 . We speculate that the negative effect of TIA on female calling behavior 22 could increase the competiveness of pheromone dispensers relative to females, which should potentiate CMD and have no net effect on NCMD. On the other hand, a negative impact of TIA on males could enhance NCMD, while it should have no effect on CMD.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that topical application of the neonicotinoid thiacloprid (TIA) substantially reduced pheromone release behaviour in females of three tortricid moth species [ Cydia pomonella (L.), Grapholita molesta (Busck) and Lobesia botrana (Denis & Schiffermüller); from here on “CP”, “GM” and “LB”, respectively], starting at the lethal concentration LC 0.001 which kills only 10 in 10 6 individuals 25,22 . In the present study, we explore the influence of TIA on male perception of, and response and orientation to sex pheromone.…”
Section: Introductionmentioning
confidence: 91%
“…The effect of insecticides on mating behaviour has generally been shown to be detrimental (Tappert, Pokorny, Hofferberth, & Ruther, ). owing to the “info‐disruptor” effect of insecticide residues (Tricoire‐Leignel et al, ) on pheromone communications as demonstrated in both pest (Evenden, Mclaughlin, & Czokajlo, ; Navarro‐Roldán & Gemeno, ) and beneficial arthropods (Wang, Lü, & He, ). A few notable exceptions have nonetheless been reported: in the pest moth Agrotis ipsilon, it was shown that a neonicotinoid insecticide enhanced the response to sex pheromones (Rabhi et al, ).…”
Section: Discussionmentioning
confidence: 99%